Oral Health Status in Children with Autism Spectrum Disorder: A Cross Sectional Study from Turkey - Oda, Gülsevim; Karayağmurlu, Ali; Dağlı, Işıl; Aren, Gamze; Soylu, Nusret (My University, 2021)
Abstract Y Objective: In this study, it was aimed to investigate the oral and dental health status of children with Autism Spectrum Disorder (ASD) and the clinical and sociodemographic factors that might be associated with it. Methods: This cross-sectional study included 83 children with ASD (3-18 years old). ASD diagnosis was based on DSM-5 criteria. Autism Behavior Checklist (ABC) and Personal Information Form were filled by the parents. Oral examination of each patient was performed by the same experienced dentist and the presence of dental caries and dental plaque was recorded. Results: The mean +/- SD age of subjects was 8.10 +/- 4.14 years and the male gender was 78.3% (n = 65). It was determined that 81.9% of the patients had caries and the mean total DMFT/dmft value of the subjects was 4,75 +/- 3,66. In the linear multiple regression model, the relationship of the child's age (p = 0.0) and the ABC total score (p = 0.02) to the DMFT score were found statistically significant. Conclusion: Healthcare professionals should take into consideration that dental health problems can be observed more in cases that show the symptoms of ASD are severe. It would be beneficial for them to adopt a multidisciplinary approach in the management of cases during the evaluation process.
Keywords: Autism Spectrum Disorder; Children; Dental Care; Oral Health